The Influence of Electronic Word of Mouth and Hedonic Shopping Motives on Impulse Buying in Shopee Flash Sales Users: A Study on Shopee Users in Malang City - Fitriani, Nur Afika; Zagladi, Arief Noviarakhman (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
With the increasing number of internet users in Indonesia, people are starting to experience changes in behavior and mindset, whereas modern society prefers practical and efficient things. One of the changes in people's behavior is in terms of shopping, previously, people preferred to shop directly by coming to the store they wanted to visit and of course, it would take a long time or process, in contrast to now that people prefer to shop online with a shorter time or process using e-commerce. This study was conducted to examine the factors that influence consumer behavior in making impulse purchases on Shopee. Factors that influence impulse buying on Shopee are thought to be influenced by electronic word of mouth and hedonic shopping motives. This study uses quantitative research using IBM SPSS 26. A sample of 100 questionnaires was distributed to respondents, with the assumption that if more than 30 questionnaires were filled in. The results show that electronic word of mouth has no effect on impulse buying, hedonic shopping motives affect impulse buying, and simultaneously electronic word of mouth and hedonic shopping motives affect impulse buying. Keywords: Electronic Word Of Mouth, Hedonic Shopping Motives, Impulse Buyinga